Margaret McWilliams : an interwar feminist - Kinnear, Mary, 1942- (McGill-Queen's University Press, 1991)
McWilliams began her career in public life when she arrived in Winnipeg at the age of thirty-five. A graduate in Political Science from the University of Toronto, she had a vision of women university graduates as "pilgrims of peace abroad and pilgrims of understanding at home." During her years in Winnipeg she became the first president of the Canadian Federation of University Women, wrote a number of books on history and politics, served as a city councillor during the Depression, and in 1943 chaired the subcommittee on Postwar Problems for Women for the federal government's committee on Reconstruction. For more than thirty years she held regular "current events" classes, providing education in politics for women. Central to Kinnear's study is a definition of feminism with three core components: women are equal to men and ought not to be treated as inferior; the condition of women is socially constructed and can be altered by human choice; and women experience a consciousness of identification with other women as a social group. Any definition of feminism is bound to be contentious but one is necessary, Kinnear maintains, if comparisons are to be made over time and across cultures. Kinnear also discusses the notion of class and its relationship to gender and ethnicity in the interwar period. Margaret McWilliams is being published during the seventy-fifth anniversary of the enfranchisement of women in Manitoba, Saskatchewan, and Alberta, the first provinces to do so. Margaret McWilliams, the woman, was an exemplary model of women in post-suffrage public life.